Jet Cross Pendants from the British Isles and Beyond: Forms, Distribution and Use. (November 2013) - Pierce, Elizabeth
Abstract : CROSS PENDANTS, decorated with a ring-and-dot motif and made out of Whitby jet, have been found as far away as Norway and Greenland. This paper catalogues this unique group of artefacts and discusses their context. Their distribution is centred in Yorkshire, suggesting that they were made at Whitby Abbey in the late 12th century. Combining the power of the Christian cross with the magical properties of jet, they were likely worn as protective amulets.